Analisis Learning Obstacle pada Konsep Luas Permukaan Kubus dan Balok siswa Kelas VIII SMP Islam Pariskian - Apriansyah, Muhammad Fahmi; Sukirwan, Sukirwan; Jaenudin, Jaenudin (Universitas Pendidikan Mandalika (UNDIKMA), 2023)
To achieve a mathematics learning goal, it is necessary to understand a mathematical concept to make it easier to determine a solution. However, in class learning there are still difficulties in achieving these learning objectives, especially area of surface cube and cuboid. One of the difficulties of students occurs because of the existence of learning obstacles for students known as Learning Obstacles. The research design in this study uses a qualitative method by identifying learning obstacles of area of surface cube and cuboid. Based on the results and discussion, there are findings of learning obstacles identified by students on the area of surface cube and cuboid from each indicator. From these learning obstacles, there are three causes of these learning obstacles. First, Ontogenical Obstacle which occurs due to mental unpreparedness of students when going to receive learning. Second, the didactical obstacle where the teaching materials used by the teacher do not clearly explain the concept of cube and cuboid spaces and only display the formulas of each problem Third, the epistemological obstacle which occurs due to the teacher's execution process in conducting learning. Because the book used does not describe the concept of cube and cuboid plus the lack of creativity from the teacher in conveying the concept of cube and cuboid.